Carnosic acid induces apoptosis of hepatocellular carcinoma cells via ROS-mediated mitochondrial pathway - Zhang, Xinrui; Chen, Yiling; Cai, Guangsheng; Li, Xin; Wang, Di (Chemico-biological interactions, 2017)
Carnosic acid (CA), an important bioactive phenolic diterpene mainly found in labiate plants, exerts various biological functions, including antioxidant, anti-inflammatory, antitumor, and neuroprotective activities. In the present study, we proved the deleterious effects of CA against hepatocellular carcinoma (HCC) in both in vitro and in vivo models. In vitro, CA significantly decreased cell viability, inhibited cell proliferation and migration, enhanced apoptosis, and increased caspase-3, -8, and -9 activities in HepG2 and SMMC-7721 cells. Specifically, CA led to a decreased mitochondrial membrane potential (MMP) and increases in intracellular reactive oxygen species (ROS) levels and apoptosis-related protein expression. Pre-incubation of HCC cells with N-Acetyl-l-cysteine (NAC), a ROS inhibitor, strongly suppressed CA-induced apoptotic phenomena, including reduced cell viability, excessive ROS levels, MMP decreases, and abnormal protein expression, suggesting an association of CA-induced apoptosis with oxidative stress-mediated mitochondrial pathways. In HepG2-and SMMC-7721-xenograft tumor mouse models, treatment with CA inhibited tumor growth and modulated apoptosis-related protein expression, confirming the anti-HCC effects of this chemical. Moreover, the CA-mediated anti-HCC effects associated with oxidative stress provide experimental evidence to support the potential use of CA as a drug therapy for HCC. •Carnosic acid (CA) induces apoptosis in hepatocellular carcinoma cells.•CA inhibited the growth of HepG2-and SMMC-7721-xenografted tumor in mice.•CA-induced HCC cell apoptosis via oxidative stress-mediated mitochondrial pathway.•CA regulates the phosphorylation of NF-κB and mTOR involved in its pro-apoptosis.